Xenon Improves Neurologic Outcome and Reduces Secondary Injury Following Trauma in an In Vivo Model of Traumatic Brain Injury*. Issue 1 (January 2015) - Campos-Pires, Rita; Armstrong, Scott P.; Sebastiani, Anne; Luh, Clara; Gruss, Marco; Radyushkin, Konstantin; Hirnet, Tobias; Werner, Christian; Engelhard, Kristin; Franks, Nicholas P.; Thal, Serge C.; Dickinson, Robert
<x xml:space="preserve">Abstract</x> Objectives: To determine the neuroprotective efficacy of the inert gas xenon following traumatic brain injury and to determine whether application of xenon has a clinically relevant therapeutic time window. Design: Controlled animal study. Setting: University research laboratory. Subjects: Male C57BL/6N mice (n = 196). Interventions: Seventy-five percent xenon, 50% xenon, or 30% xenon, with 25% oxygen (balance nitrogen) treatment following mechanical brain lesion by controlled cortical impact. Measurements and Main Results: Outcome following trauma was measured using 1) functional neurologic outcome score, 2) histological measurement of contusion volume, and 3) analysis of locomotor function and gait. Our study shows that xenon treatment improves outcome following traumatic brain injury. Neurologic outcome scores were significantly (p < 0.05) better in xenon-treated groups in the early phase (24 hr) and up to 4 days after injury. Contusion volume was significantly (p < 0.05) reduced in the xenon-treated groups. Xenon treatment significantly (p < 0.05) reduced contusion volume when xenon was given 15 minutes after injury or when treatment was delayed 1 or 3 hours after injury. Neurologic outcome was significantly (p < 0.05) improved when xenon treatment was given 15 minutes or 1 hour after injury. Improvements in locomotor function (p < 0.05) were observed in the xenon-treated group, 1 month after trauma. Conclusions: These results show for the first time that xenon improves neurologic outcome and reduces contusion volume following traumatic brain injury in mice. In this model, xenon application has a therapeutic time window of up to at least 3 hours. These findings support the idea that xenon may be of benefit as a neuroprotective treatment in patients with brain trauma.